2002
DOI: 10.1021/jf020095j
|View full text |Cite
|
Sign up to set email alerts
|

Ability of Lipid Hydroperoxides To Partition into Surfactant Micelles and Alter Lipid Oxidation Rates in Emulsions

Abstract: Lipid hydroperoxides are important factors in lipid oxidation due to their ability to decompose into free radicals. In oil-in-water emulsions, the physical location of lipid hydroperoxides could impact their ability to interact with prooxidants such as iron. Interfacial tension measurements show that linoleic acid, methyl linoleate, and trilinolein hydroperoxides are more surface-active than their non-peroxidized counterparts. In oil-in-water emulsion containing surfactant (Brij 76) micelles in the continuous … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
103
3
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 131 publications
(109 citation statements)
references
References 13 publications
(16 reference statements)
2
103
3
1
Order By: Relevance
“…As such, surface-active LOOHs could concentrate at the oil-water interfaces of bulk oils, oil-in-water emulsions, or membrane systems. Indeed, several authors have reported the presence of LOOH at the emulsion droplet surface (Dimakou et al 2007;Mancuso et al 2000;Mei et al 1998a,b;Nuchi et al 2002;Yoshida & Niki 1992). In membrane systems, LOOHs float on the LDL surface (Ingold et al 1993).…”
Section: Self-assembly Of Lipid Hydroperoxides As a Trigger Of The Prmentioning
confidence: 99%
See 3 more Smart Citations
“…As such, surface-active LOOHs could concentrate at the oil-water interfaces of bulk oils, oil-in-water emulsions, or membrane systems. Indeed, several authors have reported the presence of LOOH at the emulsion droplet surface (Dimakou et al 2007;Mancuso et al 2000;Mei et al 1998a,b;Nuchi et al 2002;Yoshida & Niki 1992). In membrane systems, LOOHs float on the LDL surface (Ingold et al 1993).…”
Section: Self-assembly Of Lipid Hydroperoxides As a Trigger Of The Prmentioning
confidence: 99%
“…Twenty-eight formulations were associated with an estimated proportion of unadsorbed emulsifiers higher than 90%; 20 resulted in an unadsorbed proportion of 70-90%, and 13 in an unadsorbed proportion of 50-70%. There is abundant experimental evidence from studies using oil-in-water emulsions and microemulsions that unadsorbed surfactants present in the aqueous phase at concentrations higher than their critical micelle concentration (CMC) serve as vehicles for transferring antioxidants (Kiralan et al 2014;Laguerre et al 2009Laguerre et al , 2010Panya et al 2012;Richards et al 2002), hydroperoxides (Nuchi et al 2002), and iron (Cho et al 2002) from the oily phase to the aqueous one and/or the interface.…”
Section: Mass Transfer Phenomena In Lipid Dispersions: a Working Hypomentioning
confidence: 99%
See 2 more Smart Citations
“…Addition of a hydroperoxyl group to a phospholipid or cholesteryl ester molecule strongly increases hydrophilicity. As a result, LOOH molecules are more surface active than their non-peroxidised counterparts (Nuchi et al 2002). Their exposure to the aqueous phase at the HDL surface facilitates their removal from the lipoprotein.…”
Section: Mechanisms Of Protectionmentioning
confidence: 99%